Properties of Lignin from Oil Palm Empty Fruit Bunch and Its Application for Plywood Adhesive - Risanto, Lucky; Hermiati, Euis; Sudiyani, Yanni (Makara Journal of Technology, 2014)
Lignin from lignocellulosic biomass is a potential biopolymer for wood adhesive. The aims of this study were to characterize lignin isolated from the black liquor of oil palm empty fruit bunch fiber pretreated with steam explosion in alkaline conditions and to examine the bond quality of aqueous polymer isocyanate (API) adhesive prepared from lignin, natural rubber latex (NRL), and polyvinyl alcohol (PVA) as base polymers with isocyanate crosslinkers. Lignin was precipitated from the black liquor by adding hydrochloric acid; then the precipitate was separated by filtration, thoroughly washed with water up to pH 2 and pH 5, and dried. The isolated lignin was characterized by ultimate analysis, UV spectroscopy, FT-IR spectroscopy, and thermal analysis. Three-layer plywood samples were prepared, and the bond strengths of the plywood samples were determined in dry conditions and after cyclic boiling. The lignin isolates with different pH values did not have significantly different chemical and thermal properties. Both lignin isolates had similar C, H, and O contents, identical functional groups in the FTIR spectra, similar absorption in the UV spectra, and high decomposition temperatures. The base polymers composition that could produce API adhesive for exterior applications was NRL/PVA/lignin (4/4/2). The use of more lignin in the adhesive formulation decreased the bond strength of the plywood.